Bidirectional Echolocation in the Bat Barbastella barbastellus: Different Signals of Low Source Level Are Emitted Upward through the Nose and Downward through the Mouth. - Anna-Maria Seibert; Jens C Koblitz; Annette Denzinger; Hans-Ulrich Schnitzler (PLoS ONE, 2015)
The Barbastelle bat (Barbastella barbastellus) preys almost exclusively on tympanate moths. While foraging, this species alternates between two different signal types. We investigated whether these signals differ in emission direction or source level (SL) as assumed from earlier single microphone recordings. We used two different settings of a 16-microphone array to determine SL and sonar beam direction at various locations in the field. Both types of search signals had low SLs (81 and 82 dB SPL rms re 1 m) as compared to other aerial-hawking bats. These two signal types were emitted in different directions; type 1 signals were directed downward and type 2 signals upward. The angle between beam directions was approximately 70°. Barbastelle bats are able to emit signals through both the mouth and the nostrils. As mouth and nostrils are roughly perpendicular to each other, we conclude that type 1 signals are emitted through the mouth while type 2 signals and approach signals are emitted through the nose. We hypothesize that the "stealth" echolocation system of B. barbastellus is bifunctional. The more upward directed nose signals may be mainly used for search and localization of prey. Their low SL prevents an early detection by eared moths but comes at the expense of a strongly reduced detection range for the environment below the bat. The more downward directed mouth signals may have evolved to compensate for this disadvantage and may be mainly used for spatial orientation. We suggest that the possibly bifunctional echolocation system of B. barbastellus has been adapted to the selective foraging of eared moths and is an excellent example of a sophisticated sensory arms race between predator and prey.